Financial information use in parliamentary debates in a changing context - Jorge, S.; Nogueria, S.; Jesus, M. A. (Public Organization Review, 2023)
Applying quantitative and qualitative content and sentiment analysis, this study investigates the use of financial information by politicians in the Portuguese parliament, in a changing context. There is clear preference for Budgetary Information. A change in the political majority in Parliament and an improvement in the country’s economic and financial situation affect the intensity and intentions of using financial information by politicians – the use with positive sentiments of those government-related, to legitimize their policies, and with negative sentiments when they pass to the opposition, using it as ammunition or to divert attention from measures implemented when they were in power.